Decomposing complex thin-walled CAD models for hexahedral-dominant meshing. (October 2018) - Sun, Liang; Tierney, Christopher M.; Armstrong, Cecil G.; Robinson, Trevor T.
Abstract: This paper describes an automatic method for identifying thin-sheet regions (regions with large lateral dimensions relative to the thickness) for complex thin-walled components, with a view to using this information to guide the hexahedral (hex) meshing process. This fully automated method has been implemented in a commercial CAD system (Siemens NX) and is based on the interrogation and manipulation of face pairs, which are sets of opposing faces bounding potential thin-sheet regions. Careful consideration is given to the mapping, merging and intersection of face pairs to generate topologies suitable for sweep meshing the thin-sheet regions, and for treating the junctions between adjacent thin-sheet regions. It is proposed that hex meshes be applied to thin-sheet regions by quad meshing one of the faces bounding the thin-sheet region and sweeping it through the thickness to create hex elements. Decisions on the generation and positioning of the cutting surfaces required to isolate thin-sheet regions are made by considering the likely impact on the quality of the resulting mesh. The method delivers a substantial step towards automatic hex meshing for complex thin-walled geometries. A significant reduction of the degrees of freedom (DOF) can be achieved by applying anisotropic hex elements to the identified thin-sheet regions. Highlights: A novel approach for decomposing CAD models for hex meshing is described. The approach has been implemented within a commercial CAD system (NX). The approach has been tested on industrial aero engine models. Offsetting of splitting surfaces is performed to provide good quality hex.